Answer :

To prove that x(x+1)^{2}y_{2}+(x+1)^{2}y_{1} = 2

We will use and

We know that log(a/b) = log a – log b

⇒ y = log (x + 1)^{2} – log x

As log x^{n} = n log x

⇒ y = 2 log (x + 1) – log x

Differentiate with respect to x

Differentiate again with respect to x

Using u/v rule

Multiply (x+1) to both numerator and denominator in to get,

Using (i)

⇒ y_{2}(x + 1)^{2}x = 2 – (x + 1)^{2}y_{1}

⇒ y_{2}(x + 1)^{2}x + (x + 1)^{2}y_{1} = 2

Hence proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Which of the follMathematics - Exemplar

Family y = Ax + AMathematics - Exemplar

The order and degMathematics - Exemplar

If y = 3e^{2x<}Mathematics - Board Papers

Write the degree Mathematics - Board Papers

The degree of theMathematics - Exemplar